Diversity of bacterial communities in the rhizosphere of the endangered plant, Paeonia jishanensis - Wang, Dong-sheng; Erihemu, Erihemu; Yang, Bin (Archives of Biological Sciences, 2019)
Paper description: Paeonia jishanensis is a significant ancestral species and many cultivated tree peony species were bred from it. P. jishanensis is also a traditional Chinese herbal medicine. The species is facing extinction. This study describes for the first time the rhizosphere microbial communities of P. jishanensis with a different growth status. Our work suggests that the abundance of many potentially beneficial rhizospheric microbes have decreased with the decline of the plant. Inoculation of beneficial microbes could be a potential approach to protect those endangered plants. Abstract: The microbial community in the rhizosphere is thought to provide plants with a second set of genomes, which plays a pivotal role in plant growth. In the present study, soil samples were collected from the rhizosphere of an endangered plant, Paeonia jishanensis. The plants were divided into three groups: well-growing plants, poor-growing plants and dead plants. Metagenomic DNA was isolated from rhizosphere soil samples of these plants and 16S rRNA genes were sequenced by the PacBio-RS II system. The results of taxonomic analysis showed that the dominant phyla were Proteobacteria, Acidobacteria, Planctomycetes, Bacteroidetes and Actinobacteria in all three sample types. Linear discriminate analysis Effect Size (LEfSe) showed that 5 species, Hirschia baltica, Arcobacter aquimarinus, Gimesia maris, Magnetococcus marinus and Pseudoxanthobactor soli, were significantly enriched in the rhizosphere of well-growing plants. Additionally, the results of PCA, MDS and clustering analysis indicated that the bacterial community in the rhizosphere of living P. jishanensis plants was similar. With the death of plants, the bacterial community changed considerably. These findings suggest that the abundance of many beneficial rhizospheric microbes declined with the death of P. jishanensis. This is a potential way to preserve endangered plants by inoculating declining species with beneficial microbes. https://doi.org/10.2298/ABS190203036W Received: February 3, 2019; Revised: May 29, 2019; Accepted: May 31, 2019; Published online: June 7, 2019 How to cite this article: Wang DS, Erihemu, Yang B. Diversity of bacterial communities in the rhizosphere of the endangered plant, Paeonia jishanensis. Arch Biol Sci. 2019;71(3):525-31.